ANALISIS FENOMENA JANUARY EFFECT PADA INDEKS SAHAM LQ 45 - Ombri Absalom (2021)
The purpose of this study is to determine the phenomenon of market anomalies that occur in the LQ-45. This phenomenon is an event where every January there is an increase in the stock price and is usually called the January Effect. The variables used in this study are Abnormal Return and Trading Volume Activity. The sampling method used is Saturated Sample, that is, all LQ-45 members are sampled during the 2016-2020 period. The hypothetical test used is the One Way Anova Test. The results of this study indicate that there is no January Effect phenomenon and there is no difference between Abnormal Return and Trading Volume Activity in January compared to other months on the LQ-45 index on the Indonesia Stock Exchange.